1993
DOI: 10.3181/00379727-202-43564
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Clusterin in Chronic Nephrotoxicity in the Rat

Abstract: The excretion of clusterin was compared with that of N-acetyl-beta-glucosaminidase (NAG) in rats given gentamicin daily for 2 months to determine whether clusterin excretion stays elevated after NAG excretion falls during chronic gentamicin administration. Clusterin was measured by radioimmunoassay and NAG by the hydrolysis of 4-methylumbelliferyl-N-acetyl-beta-D-glucosaminide. Gentamicin at 110 mg/kg was given daily for 44 days and thereafter, at 90 mg/kg daily. The excretion rate of both proteins rose rapidl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 0 publications
1
10
0
1
Order By: Relevance
“…In the kidney, clusterin is found prominently only in the early stages of nephron development (French et al 1993;Harding et al 1991), but it reappears after various types of acute and chronic injury (Buttyan et al 1989;Correa-Rotter et al 1992;Cowley and Rupp 1995;Harding et al 1991;Nath et al 1994;Obermüller et al 1997;Pearse et al 1992;Rosenberg and Paller 1991;Witzgall et al 1994). Since urinary excretion of clusterin increases after gentamicin-induced acute renal failure (Aulitzky et al 1992;Eti et al 1993), we have hypothesized that it could also be used as a valuable laboratory marker of renal ischemia-reperfusion damage. Furthermore, we have tested its use in a hereditary model of renal disease, i.e., the (cy/+) rat model of ADPKD, which slowly develops chronic renal failure.…”
Section: Discussionmentioning
confidence: 94%
“…In the kidney, clusterin is found prominently only in the early stages of nephron development (French et al 1993;Harding et al 1991), but it reappears after various types of acute and chronic injury (Buttyan et al 1989;Correa-Rotter et al 1992;Cowley and Rupp 1995;Harding et al 1991;Nath et al 1994;Obermüller et al 1997;Pearse et al 1992;Rosenberg and Paller 1991;Witzgall et al 1994). Since urinary excretion of clusterin increases after gentamicin-induced acute renal failure (Aulitzky et al 1992;Eti et al 1993), we have hypothesized that it could also be used as a valuable laboratory marker of renal ischemia-reperfusion damage. Furthermore, we have tested its use in a hereditary model of renal disease, i.e., the (cy/+) rat model of ADPKD, which slowly develops chronic renal failure.…”
Section: Discussionmentioning
confidence: 94%
“…Several years ago, the potential importance of serum clusterin was written in the diagnosis of renal disorders; many patients with renal disorders had lower urinary clusterin, which was considered as one cause of renal diseases (e.g. clusterin defi ciency leads to activation of complement cascade and thus to possible renal injury) [5][6][7][8][9][10][11] . On the other hand, there is experimental evidence that individuals with impaired renal parenchyma or toxic injury have higher urinary clusterin concentrations (together with other proteins) 6,10,12 .…”
Section: Discussionmentioning
confidence: 99%
“…clusterin defi ciency leads to activation of complement cascade and thus to possible renal injury) [5][6][7][8][9][10][11] . On the other hand, there is experimental evidence that individuals with impaired renal parenchyma or toxic injury have higher urinary clusterin concentrations (together with other proteins) 6,10,12 . This is interesting apropos clusterin production by a stressed cell; enhanced urinary clusterin levels could be permanent and independent of diuresis changes or renal perfusion 4,6 .…”
Section: Discussionmentioning
confidence: 99%
“…27) Clusterin (CLUS), which was also newly induced in rats treated with high-dose CsA, is a heterodimeric glycoprotein induced after renal tubular cell injury. [30][31][32][33] Although there are a few reported studies on CsA nephrotoxicity inducing CLUS, 30) a great number of publications have reported the function of CLUS in the physiology and pathology of the kidney. [31][32][33][34] The basal expression of CLUS in the kidney is minimal and confined to rare distal tubular cells, but it is markedly induced in a variety of tubular injury states.…”
Section: Identification Of Proteinsmentioning
confidence: 99%
“…[30][31][32][33] Although there are a few reported studies on CsA nephrotoxicity inducing CLUS, 30) a great number of publications have reported the function of CLUS in the physiology and pathology of the kidney. [31][32][33][34] The basal expression of CLUS in the kidney is minimal and confined to rare distal tubular cells, but it is markedly induced in a variety of tubular injury states. 32) Numerous functions have been proposed for CLUS, including complement inhibition, lipid transport, apoptosis, membrane protection, and maintenance of normal cell interactions.…”
Section: Identification Of Proteinsmentioning
confidence: 99%